До питання про час і місце народження Володимира Антоновича - Петренко, О. (Архіви України, 2008)
On the basis of the documents of the State Archives of Vinnytsia Oblast the author clarifies the date and place of birth of Volodymyr Antonovych, an outstanding Ukrainian historian.